The Effect of Chain Tacticity on the Thermal Conductivity of Isotactic and Syndiotactic Polystyrene - Taha, Dalmn Y.; Ahmed, Israa Z.; Mohammed, Tawfeeq (Journal of Engineering and Technological Sciences, 2025)
This study looks into the influence of tacticity on the heat conduction through isotactic and syndiotactic polystyrene. The experimental work includes the collection of five different batches of polystyrene pellets with different tacticity. The molecular weight, isotacticity index and coefficient of thermal conductance were measured using gel permeation chromatography (GPC), nuclear magnetic resonance (NMR) and thermal conductivity apparatus, respectively. The results have indicated that there are relationships between these parameters for certain conditions. The obtained data show that isotacticity index enhanced by increasing the molecular weight of polystyrene. Subsequently, the isotacticity index affected the value of thermal conductivity of polystyrene. It was observed that the decrease of isotacticity in the syndiotactic polystyrene leads to reduce its thermal conductivity by 15-20%. But, the thermal conductivity of syndiotactic polystyrene is still higher than that of isotactic mode by 30-40% in average. The NMR analysis shows that the presence of random phenyl groups in the polymer decreases its isotacticity